Efektivitas Penggunaan Media Pembelajaran Audio Visual Lcd (Liquid Crystal Display) Proyektor Dalam Keterampilan Menulis Iklan Pada Siswa Kelas VIII SMP IT Sunan Gunung Jati : Tahun Ajaran 2024/2025 - Hasafitri, Dini (PT. Alahyan Publisher Sukabumi, 2024)
This research aims to determine the effectiveness of using audio-visual learning media on the advertising writing skills of class VIII SMP IT Sunan Gunung Jati students. The type of research carried out is quantitative research. Through 3 stages, namely starting from the Pretest in the form of giving skills tests, treatment in the form of applying the use of audio visual learning media and Posttest in the form of giving skills tests again. The data collection tool uses a Skills Test. The research results showed that students' advertising writing skills test scores at the pretest stage obtained an average percentage of 56.30% and continued at the posttest stage obtained an average percentage of 87.96%. These data show that the effectiveness of using audio-visual learning media can improve students' advertising writing skills in class VIII SMP IT Sunan Gunung Jati.